Carbon allocation patterns in forbs and grasses differ in responses to mowing and nitrogen fertilization in a temperate grassland. (February 2022) - Zhang, Lulu; Yang, Liuyi; Zhou, Huirong; Ren, Lifei; Li, Wenchao; Bai, Wenming; Zhang, Wen-Hao
Highlights: C allocation involves plant growth and responses to changing environments. Mowing and N fertilization did not affect C accumulation at community level. Mowing and N fertilization enhanced C accumulation in forbs and grasses. Mowing increased 13 C allocation to stolon of forb species. N fertilization increased 13 C allocation to rhizome of grass species. Abstract: Mowing has been a routine grassland management with consequences of removing nutrients from the nitrogen (N)-limited grassland ecosystems. Carbon (C) allocation plays important roles in plant growth and responses to changing environments. Despite studies on interactions between N fertilization and mowing, no studies have specifically focused on responses of C allocation priorities to N fertilization and mowing at plant functional groups and individual species levels. In the present study, 13 C isotope labelling was used to trace the effects of 3-year of N fertilization and mowing on the fate of newly-assimilated C (accumulation and allocation priorities) at community, functional group and species levels in a temperate grassland of northern China. We applied the allometric allocation theory to explain the differential C allocation patterns among the organs of different species. Mowing and N fertilization for three consecutive years had no impacts on accumulation of newly-assimilated C at community level. However, C allocation in forbs and grasses differed markedly in their responses to mowing and N fertilization, such that mowing enhanced C accumulation in forbs and N fertilization enhanced C accumulation in grasses. In addition, mowing increased 13 C allocation to stolon of forb species, thus facilitating their propagation. Moreover, N fertilization increased 13 C allocation to rhizomes of grass species, ensuring clonal grasses to occupy a new niche. We demonstrated that grasses and forbs in a temperate grassland evolved different strategies of C allocation in response to mowing and N fertilization. The contrasting responses may account for the observation that N fertilization and mowing had no impacts on C accumulation at the community level. Our results highlight the necessity to monitor C allocation at functional group and dominant plant species levels, rather than at community level of grasslands exclusively for mechanistically understanding how grasslands respond to mowing and N fertilization.